ORGINAL ARTICLEShort-term treatment with rivastigmine and plasma levels of Ab peptides in Alzheimer’s disease - Sobow, Tomasz; Kloszewska, Iwona (Folia Neuropathologica, 2005)
Deregulation of APP metabolism is considered to be a key pathogenic event in Alzheimer’s disease. Data from cell cultures indicate that the secretion of Ab1-42 might be inhibited by cholinesterase inhibitors, possibly via M1 receptors stimulation. Treatment with tacrine, a dual acetyl- and butyrylcholinesterase inhibitor, had no significant effect on mean plasma Ab species concentrations. However, a correlation was observed between higher drug concentrations and lower Ab levels that might indicate an effect on APP metabolism with an increased a-cleavage. Ab1-40 and Ab1-42 levels were measured in the plasma of 28 AD subjects by means of a commercially available ELISA before rivastigmine treatment and at week 2 after the first dose of the drug (3 mg/day) had been administered. Treatment with rivastigmine exhibited a significant effect on mean plasma concentrations of Ab1-42 (mean difference 7.8±8.4, t=-4.9, pmean difference 7.8±8.4, t=-4.9, p<0.001) with a negative correlation with the patients age (Pearson\'s R=-0.40, p=0.035). No significant effect on plasma Ab1-40 was observed. The observed increase of mean levels of plasma Ab1-42 after rivastigmine treatment might indicate an effect of the drug on Ab metabolism, mobilization of Ab1-42 from deposits in the affected brain areas and a consecutive Ab1-42 brain-to-plasma efflux. The negative correlation between Ab1-42 plasma levels changes and age may be a sign of impairment of this process in the older patients. A large individual variation of the observed response, however, excludes drawing definite conclusions. Whether those subjects who respond to rivastigmine in terms of Ab1-42 plasma levels changes also respond clinically needs to be established.